Tommaso Stanislao Velasti’s Battle(s) for the Greek Language: The Case of his Frangochiotika - Psalti, Mara (The Historical Review/La Revue Historique, 2025)
This article discusses the Frangochiotic corpus of Tommaso Stanislao Velasti, a prolific Jesuit scholar and writer hailing from the island of Chios (1717–1773), within the broader context of his advocacy for the Greek language, both ancient/classical and vernacular. It examines the linguistic intricacies of his allography, with a focus on two key works: Anapavsis tis cardhias (Rome, 1746), a translated manual of spiritual theology, and Psichofelis loji (Messina, 1753), an original collection of meditative sermons. The study includes a comprehensive typological analysis of his allographic systems, exploring the correspondences between Latin and Greek scripts, and investigates how his allography reflects the contemporary dialect of Chios. The article posits that Frangochiotika not only mirrors Velasti’s overarching aspiration to champion his native Chiot dialect but is also paradoxically incorporated into a pioneering proposal – modeled after Dante and Petrarch – for the standardisation of vernacular Greek.